Care of the Self in Couchsurfing : Practices of a Host in the Intimately Mobile Age. - Cook, Lauren (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis examines the practices of ‘care of the self’ undertaken by Couchsurfing hosts- the particular practices involved in being a host and the role of ‘care of the self’ in Couchsurfing relationships. The concept of ‘care of the self’ is developed from Michel Foucault’s ‘technologies of the self’, and refers to the ways in which individuals come to understand, regulate and develop themselves (both alone and through interaction with others). I identified seven practices of ‘care of the self’: reason, interacting with others, self-representation, reflection and examination, relation to self (especially in the form of self-knowledge), health (of body and soul), and self-improvement. Using a mixed methodology of autoethnography, interviews and questionnaires, I drew on both my own experiences as a host in the Couchsurfing community, as well as those of my Couchsurfing guests (or ‘surfers’). I kept an autoethnographic diary of my experiences from late 2016 to early 2017, during which time I hosted eight guests. These same eight guests also participated in semi-structured interviews, offering insights into their own experiences with previous hosts, or as hosts themselves. The questionnaires are used in discussion of the ‘pre-meeting period’, to analyse the self-representation of Couchsurfing members in their online profiles. My results show that reason is the key practice of ‘care of the self’ for Couchsurfing hosts, as it is present at every stage of the Couchsurfing interaction and also determines which other practices the host will utilise. Each of the seven practices are shown to be used by hosts at different times of the Couchsurfing interaction.